Effects of Mirabegron vs Tamsulosin in Reducing Lower Urinary Tract Symptoms in patients with Indwelling Double J Stents - Hafiz Muhammad Yousaf Khan, Ahmed Raza, Jamshed Rahim, Muhammad Rameez, Syed Umer Farooq, Ubaid-ur-Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the mean IPSS score after treatment with tamsulosin versus mirabegron in patients with double J stent related lower urinary tract symptoms. Study design: Randomized controlled trial. Place and duration of study: Department of Urology Shaikh Zayed Hospital, Lahore from 2nd May 2019 to 1st November 2019. Methodology: One hundred patients of both genders aged between 18-60 years having DJ stent related symptoms (IPSS score ≥7) were enrolled. Patients were randomized into 2 groups based on treatment. Patients in Group A were given mirabegron while the one in Group B were treated with tamsulosin. Outcome variable was mean IPSS score 3 weeks after treatment which was noted and compared between the groups. Results: The mean age was 38.6±10.9 years. There were 59 (59.0%) male and 41 (41.0%) female patients with a male to female ratio of 1.4:1. The IPSS score at baseline ranged from 14 to 23 with a mean of 18.18±2.77. The follow-up IPSS score was significantly lower in patients treated by mirabegron as compared to tamsulosin (6.28±0.86 vs. 9.60±0.86; p-value<0.001). Similar significant difference was noted between the groups across various subgroups based on patient’s age, gender and baseline IPSS score. Conclusion: Mirabegron was superior to conventional practice of tamsulosin in the treatment of DJ stent related symptoms in terms of significantly lower mean IPSS score after 3 weeks of treatment. Keywords: DJ stent, Lower urinary tract symptoms, Mirabegron, Tamsulosin